One-step synthesis of α-Fe2O3–δ as promising anode materials for high performance lithium-ion batteries. (1st February 2018) - Zeng, Peiyuan; Qian, Fangfang; Lin, Yingwu; Wang, Xiaoxiao; Li, Jianwen; Wang, Wanwan; Tao, Feng; Fang, Zhen
Abstract: Flower-like α -Fe2 O3− δ nanostructures have been successfully synthesized via a one-step hydrothermal method. The as-prepared α -Fe2 O3− δ nanostructures exhibited a good cyclability and rate performance. The discharge capacity could retain as high as 1192.4 mAh g −1 (current density: 400 mA g −1 ) after 800 cycles, which is higher than the theoretical value of hematite. When the current density increased to 3200 mA g −1, the reversible capacity is about 660 mAh g −1 . The good electrochemical performance of α -Fe2 O3− δ nanostructures could be attributed to the combination of both nano-structuring strategy and oxygen vacancies in the as-prepared materials, which improve the structure mechanism strength, electric conductivity and facilitate the diffusion of Li ions.